2014
DOI: 10.1002/etc.2587
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of partition coefficients for complex environmental contaminants: Validation of COSMOtherm, ABSOLV, and SPARC

Abstract: Prediction of partition coefficients is essential for screening of environmentally relevant compounds. Prediction methods using only the molecular structure as input are especially useful for this purpose. In the present study, the authors validated 3 prediction method-COSMOtherm, ABSOLV, and SPARC-which are based on more mechanistic approaches than most other quantitative structure-activity relationships. Validation was based on a consistent experimental data set of up to 270 compounds, mostly pesticides and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 35 publications
1
45
0
Order By: Relevance
“…6,20 However, this was not surprising since eq 3 was derived from measurements of structurally diverse pesticides with two heterogeneous soils under a range of temperature and relative humidity conditions. Moreover, the rmse associated with eq 3 (based on experimentally determined K soil-air measurements) was considerably lower than that associated with estimation equations obtained using predictive software, such as ABSOLV (rmse ∼ 1 or slightly better), 21 which is often used in conjunction with poly-parameter linear free energy relationships (pp-LFERs).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…6,20 However, this was not surprising since eq 3 was derived from measurements of structurally diverse pesticides with two heterogeneous soils under a range of temperature and relative humidity conditions. Moreover, the rmse associated with eq 3 (based on experimentally determined K soil-air measurements) was considerably lower than that associated with estimation equations obtained using predictive software, such as ABSOLV (rmse ∼ 1 or slightly better), 21 which is often used in conjunction with poly-parameter linear free energy relationships (pp-LFERs).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The version of COSMOtherm we used in this study is C30_1401 with parametrization BP_TZVPD-FINE_C30_1401. In a recent article from our group, 21 we found this parametrization to perform best in a large validation effort. COSMOconf (v 3.0) was used to obtain cosmo files for storage lipids, water, and all solute molecules considered in this work.…”
Section: ■ Materials and Methodsmentioning
confidence: 92%
“…The Smoc2 gene encoded protein promotes extracellular matrix assembly and potentiates endothelial cell proliferation and migration[25], and has pro-angiogenic activity[26]. It was reported that the Smoc2 gene is indispensable for VEGF-induced vascular endothelial cells mitogenesis and tube formation[27,28]. Due to its promotive effect on angiogenesis, the Smoc2 gene may represent a useful target for inhibition of tumor progress.…”
Section: Discussionmentioning
confidence: 99%